Ser brasileiro na Polónia. Integração e identidade durante migração - Gawenda, Dominika (Studia Romanica Posnaniensia, 2019)
This article attempts to look at migration from an anthropological perspective, especially at the issues of integration and the changes seen in the identity of migrants. Motivation and readiness for change, along with the existing stereotypes and personal experiences of a migrant, constitute successful adaptation in a new place of residence. One of the most important elements of integration in a new society is the knowledge of this group’s language, it facilitates entering the community and is very important in terms of the reproduction of one’s identity in the new place of residence. The recreation of one’s identity is necessary, because a migrant is placed in a completely new reality in which his / her previous social role and status are different. The creation of identity happens in between the two concepts of familiarity and foreignness. The description of the above-mentioned topics was based on the partially structured interviews with Brazilians living in Poznań for at least 2 years. The bibliographies included form the basis of the anthropological analysis of migration.